Addition of blue pea flower (Clitoria ternatea L.) extract increase antioxidant activity in yogurt from various types of milk - Adi Sutakwa; Lana Santika Nadia; Suharman Suharman (Fakultas Pertanian Universitas Ichsan Gorontalo, 2021)
Blue pea flower (Clitoria ternatea L.) is known as the source of anthocyanin and has potential as a natural blue dye. The present study aimed to determine the effect of additional blue pea flower (BPFE) to yogurt from various types of milk. The study used dried blue pea flowers, extracted with water in 3:1 (g.L-1) ratio, at the extraction condition of 60 ˚C and 45 minutes. The fermentation was processed by adding BPFE to (A) liquid skim milk, (B) ultra-high temperature (UHT) milk, (C) pasteurized milk, (D) UHT milk with skim powder, and (E) pasteurized milk with skim powder. Then, the yogurt starter was added to all milk samples, evenly mixed and incubated for 24 hours at 37 ˚C. The fermentation of all five different milk to make plain yogurt also processed with same method without addition of BPFE. The antioxidant activity and color intensity of yogurt are evaluated to investigate the effect of BPFE in yogurt. The result showed that the plain yogurt without the addition of BPFE has antioxidant activity and increases with the addition of BPFE. Skim milk BPFE yogurt has the highest antioxidant activity (437.04 ppm) with the values of L*, a*, b* was 37.35; 2.02; -1.32, respectively. Antioxidant activity of the other BPFE yogurt, which was added with skim milk, also increased. The BPFE yogurt made from skim milk or added skim milk had higher antioxidant activity than the other types of milk.